Penerapan Metode Waterfall Pada Aplikasi Sistem Informasi Sekolah SMA Berbasis Website untuk wilayah Jakarta - Amar, Galih Qoirul; Lammada, Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of information and communication technology which influences many aspects of life and can be used to obtain various kinds of information, especially in educational information. Information media, one of which is the website, can be used to obtain existing school information. Educational elements that need to be considered are curriculum, educational content, learning and evaluation processes, teacher quality, school facilities and infrastructure, and textbooks. The educational element produces an image that arises in society, which can be a good or bad image. The application was developed using the waterfall method which was carried out in stages and in a structured manner. The data that has been collected is then analyzed and processed using UML to visualize the system. The implementation process builds a website display with HTML, CSS and JavaScript with a responsive view and builds a rest API using the visual studio code code editor. The testing phase uses the blackbox testing method to minimize errors in the system. The school information system application for the Jakarta area is expected to be a benchmark for the community to determine which school to choose, as well as a promotional medium for schools to show their quality.